Analisis Aspek-Aspek Keunggulan Daya Saing dalam Meningkatkan Kualitas Pendidikan di SDI Al-Akbar Bangsal - Hasanah, Kartini Dwi; Marno; Susilawati, Samsul; Tabrani, Ahmad (Jurnal Riset Madrasah Ibtidaiyah, 2024)
A superior school is a school that is able to bring every student to achieve their abilities in a measurable manner and can be demonstrated through their achievements. The background to writing this research is the demand for quality educational institutions which will be able to create schools that have competitive advantages. The aim of the research is to analyze aspects of competitive advantage that have been implemented at SDI Al-Akbar Bangsal in improving the quality of education. This research uses a descriptive method with a qualitative approach. Data was obtained through in-depth interviews with school principals, teachers, classroom observations, documentation, academic journals, books, articles and relevant research reports. Respondents consisted of the Principal, Deputy Principal, teachers and also staff at SDI Al-Akbar Bangsal. The results of this research show three things: first; SDI Al-Akbar Bangsal prepares for competitiveness in the 5.0 era; second; form aspects of competitive advantage at SDI Al-Akbar Bangsal; third; strategic concepts and approaches in improving the quality of education at SDI Al-Akbar Bangsal. Based on the research results, there are still limitations, namely the number of respondents is still small and there is only one SDI Al-Akbar institution so there is a lack of comparison with other institutions. It is recommended for future researchers to take more sample, this aims to have better data accuracy in their research. Researchers also recommend to institutions to always improve quality by always evaluating the superior aspects of SDI Al-Akbar.